2022
DOI: 10.1016/j.healthpol.2021.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Transformations in the landscape of primary health care during COVID-19: Themes from the European region

Abstract: The Covid-19 pandemic has dramatically impacted primary health care (PHC) across Europe. Since March 2020, the Covid-19 Health System Response Monitor (HSRM) has documented country-level responses using a structured template distributed to country experts. We extracted all PHC-relevant data from the HSRM and iteratively developed an analysis framework examining the models of PHC delivery employed by PHC providers in response to the pandemic, as well as the government enablers supporting these models. Despite t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 22 publications
2
31
0
2
Order By: Relevance
“…This means that for many of the EPC services, the primary way to examine patients with suspected COVID-19 symptoms was in an airway clinic staffed with personnel who usually work at the EPC. Though it was not shown in this study, it may be fair to assume that in many cases this resulted in EPC personnel working more than usual, as demonstrated by others [ 37 ].…”
Section: Discussionmentioning
confidence: 60%
“…This means that for many of the EPC services, the primary way to examine patients with suspected COVID-19 symptoms was in an airway clinic staffed with personnel who usually work at the EPC. Though it was not shown in this study, it may be fair to assume that in many cases this resulted in EPC personnel working more than usual, as demonstrated by others [ 37 ].…”
Section: Discussionmentioning
confidence: 60%
“…Lack of involvement of PC and poor integration with PH in the COVID-19 response has been identified in other countries. This was a key theme in a 2020 international study looking at the pandemic response in 111 countries,16–18 and has also been recognised in a number of European studies 19–21. PC frequently demonstrates agility and innovative capacity in the face of limited resources and a changing environment22 contributing to the resilience required in the face of pandemics.…”
Section: Conclusion: Lessons For Other Countriesmentioning
confidence: 91%
“…These results underline the importance of collaborative teamwork, digital solutions, identification of vulnerable groups, and improving access to address health inequalities magnified by the pandemic. The authors concluded with a declaration of an urgent need to capture learning from the pandemic that is specific to PHC services and to turn these into strategic action plans to strengthen preparedness for future outbreaks and better respond to the contemporary health challenges (Kumpunen et al, 2021). We hope that this collection goes some way to providing such learning to support the development of pandemic-ready PHC services.…”
Section: Primary Care and Covid-19mentioning
confidence: 99%